Activated Carbon Derived from Carbonization of Kevlar Waste Materials: A Novel Single Stage Method - Daniel Karthik (MDPI AG, 2021)
The augmented demands of textile materials over time have brought challenges in the disposal of substantial volumes of waste generated during the processing and end of life of such materials. Taking into consideration environmental safety due to discarding of textile waste, it becomes critical to recuperate useful products from such waste for economic reasons. The present work deals with the preparation of porous and electrically conductive activated carbon fabric by a novel single stage method of simultaneous carbonization and physical activation of Kevlar feedstock material procured from local industries, for effective electromagnetic (EM) shielding applications. The Kevlar fabric waste was directly carbonized under a layer of charcoal without any intermediate stabilization step at 800 °C, 1000 °C, and 1200 °C, with a heating rate of 300 °C/h and without any holding time. The physical and morphological properties of the activated carbon, influenced by carbonization process parameters, were characterized from EDX, X-ray diffraction, SEM analysis, and BET analysis. Furthermore, the electrical conductivity was analyzed. Finally, the potential application of the activated material for EM shielding effectiveness was analyzed at low (below 1.5 GHz) and high (2.45 GHz) frequencies. The phenomena of multiple internal reflections and absorption of electromagnetic radiations was found dominant in the case of activated carbon fabric produced at higher carbonization temperatures.